Drawing lessons from the standard treatment guidelines and essential medicines list concept in South Africa as the country moves towards national health insurance - Velisha A. Perumal-Pillay; Fatima Suleman (South African Family Practice)
The essential medicines concept is recognised as an instrument to improve medicines access and to promote cost-effective use of health resources. South Africa adopted the concept and implemented the Standard Treatment Guidelines and Essential Medicines List (STGs/EML) in 1996 when the National Drug Policy for South Africa was launched. The STGs/EML was meant to address the inequities in medicines access and use and to ensure a standard of care to all citizens, yet these inequities still exist. The implementation of the new National Health Insurance (NHI) scheme is envisaged to relieve this healthcare inequity. The STGs/EML still forms the basis of care in the public sector, but a critique of implementing this tool and lessons that can be applied from this implementation for NHI are lacking. This piece addresses these shortfalls and highlights questions surrounding the implementation of the STGs/EML.